2021
DOI: 10.1371/journal.pone.0253500
|View full text |Cite
|
Sign up to set email alerts
|

Removal of organic contaminants from wastewater with GO/MOFs composites

Abstract: Graphene oxide/metal-organic frameworks (GO/MOFs) have been prepared via solvothermal synthesis with ferrous sulfate heptahydrate, zirconium acetate and terephthalic acid for the purpose of removing organic pollutants from wastewater. The composites were analyzed using scanning electron microscopy, infrared spectrometry, and XRD. Tetracycline hydrochloride and orange II were implemented as model pollutants to evaluate the efficacy of the GO/MOFs in water purification, in which 50 mg of Zr/Fe-MOFs/GO was mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…3, the Fe-MOF material can be divided into three stages: (1) a mass loss (14.4%) between 20 • C and 300 • C, which could be attributed to evaporation of residual solvents from the sample; (2) a mass loss of 40% between 301 • C and 509 • C, mainly due to the oxidation of the metal ion [29]; (3) a mass loss leaving a residual amount of 33.9% of the original mass, which begins at 610 • C, corresponding to the destruction of the framework structure. This result indicated that the material was stable below 410 • C. In most cases, MOFs generated via synthetic reactions between metal ions and organic ligands have a more stable structure [30].…”
Section: Structural Characterizationmentioning
confidence: 90%
See 2 more Smart Citations
“…3, the Fe-MOF material can be divided into three stages: (1) a mass loss (14.4%) between 20 • C and 300 • C, which could be attributed to evaporation of residual solvents from the sample; (2) a mass loss of 40% between 301 • C and 509 • C, mainly due to the oxidation of the metal ion [29]; (3) a mass loss leaving a residual amount of 33.9% of the original mass, which begins at 610 • C, corresponding to the destruction of the framework structure. This result indicated that the material was stable below 410 • C. In most cases, MOFs generated via synthetic reactions between metal ions and organic ligands have a more stable structure [30].…”
Section: Structural Characterizationmentioning
confidence: 90%
“…The removal ability of Fe-MOFs was evaluated by using RhB as a model pollutant. Different concentrations (10,20,30,40, and 50 ppm) of RhB solutions were prepared. The Fe-MOFs of different masses were added to each solution separately and stirred in natural light.…”
Section: Removal Of Rhbmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance enchantment of MOFs, in terms of a high adsorption capacity and water stability, was identified as an emerging topic. To cater to these issues, the application of graphene [ 98 ], graphene oxides [ 99 ], nanoparticles [ 100 ], and quantum dots [ 101 ] was also observed on various research fronts.…”
Section: Emerging Research Trends In the Use Of Mof For Wastewater Tr...mentioning
confidence: 99%
“…As such, MOFs are promising alternative material candidates. They are widely used for catalysis, 26,27 carbon dioxide capture, 28 antibiotics, 29,30 energy storage, 31 adsorption and separation, [32][33][34] drug delivery, 35 wastewater treatment, [36][37][38][39][40] and other functions [41][42][43][44] due to their diversified structure, higher surface area, tunable functional groups, and permanent pores. Previous studies have shown that most MOFs use a single metal ion, which is limited in the treatment of pollutants, with often poor treatment effects.…”
Section: Introductionmentioning
confidence: 99%